An overview of pandemic Covid-19 and the repercussion to the tourism industries - Roshisham, Quratul Aini (Human Resource Management Academic Research Society, HRMARS, 2021)
Novel Coronavirus or COVID-19 is a global pandemic affecting most businesses and sectors worldwide since the first quarter of 2020. Many tour operators and workers are unemployed and leave unpaid as far as tourism is concerned. Moreover, the airline industry is a significant business that suffers severe global losses in the tourist industry. This study synthesises the current research on the tourist impact of the COVID-19 pandemic via the systemic evaluation of ten influential journals and research publications. The findings show that the tourist business of the nation was indirectly damaged, as a result of the pandemic growth, by most of the non-operated or partially shuttered sectors and industries, such as accommodation, transportation, and airlines. The report shows the worldwide tourism industry with severe repercussions since the COVID-19 pandemic halted airlines and touristic activities worldwide. This paper discusses how other countries adaptation strategies may be worth adapting by Malaysia to overcome challenges and barriers. For example, each country can overcome the problem in its approach, and one method is to help the poor financially. The Government may assist local businesses by encouraging domestic shopping to boost the economy and recommend that people support the local products and services since this would indirectly increase the country's economic growth. It also helps small businesses to address the changing demands of tourist companies and new needs not simply by cutting their taxes or through targeted investment in sustainable tourism and a sustainable economy, which is led by a new strategy. Moreover, tour operators are also aware of the need to restructure and anticipate government financial aid to solve the issue and concentrate more on shortening, persevering, and focusing on short-term rather than long-term planning, such as innovation in the pandemic Covid-19.